Spores that crush the spine in infancy: a diagnostic challenge for an infant with spinal tuberculosis. - Mohamed, Mossad Abdelhak Shaban (2019)
Introduction Spinal tuberculosis in children is an established preventable disease. Complications of the disease are devastating due to its aptitude to cause bone destruction, spinal deformity and paraplegia. We present seven months old girl with isolated gross motor regression and evolving spastic paraplegia. The case highlights the challenge with the diagnosis we encountered until confirming the final diagnosis.